FEATURES OF SURGICAL TACTICS IN CASE OF CLOTTED HEMOTHORAX - Baysariyev Shovkat Usmonovich (Research Focus International Scientific Journal, 2025)
This study investigates the clinical features and optimal surgical approaches for managing traumatic clotted hemothorax (TCH). A total of 78 cases were analyzed, with clotted hemothorax resulting from penetrating chest injuries in 32.05% of cases and closed trauma in 67.95%. Diagnostic methods included radiography, ultrasound, and MSCT, revealing varying fluid and air levels in the pleural cavity. Treatment methods ranged from conservative therapy to invasive surgical interventions. Video-assisted thoracoscopic sanitation (VATS) proved to be the most effective and minimally invasive approach, enabling comprehensive removal of clots and minimizing complications. Early diagnosis and appropriate choice of treatment play a critical role in improving patient outcomes in TCH cases.